High-Performing Peers and Female STEM Choices in School - Mouganie, Pierre; Wang, Yaojing (Journal of Labor Economics, 2020)
The purpose of this paper is to examine how social environment affects women’s STEM choices as early as high school. Using administrative data from China, we find that exposure to high-performing female peers in mathematics increases the likelihood that women choose a science track during high school, while exposure to more high-performing males decrease this likelihood. We also find that peer quality has persistent effects on college outcomes. Overall, there is little evidence of peer effects for boys. Our results suggest that girls doing well in mathematics provide an affirmation effect that encourages female classmates to pursue a STEM track.